A review of the Turkish government debt security price index - (:unkn) unknown (My University, 2012)
Finansal sistemde fon akışının gerçekleşmesine yardımcı olan piyasalardan biri de tahvil piyasalarıdır. sabit getiriyi tercih eden yatırımcıların kullandığı tahvil piyasaları uzun dönemli yatırım ve finansman stratejilerinin oluşturulması, faiz oranlan ve tahvil fiyatlarının belirlenmesine katkı sağlamaktadır. avrupa'da özet sektörün egemen olduğu tahvil piyasaları, türkiye'de devletin borçlanma ihtiyacı nedeniyle kamu sektörünün yüksek bir paya sahip olduğu piyasa görünümündedir. bu piyasada tek endeks olan devlet iç borçlanma senetleri fiyat endeksi, tahvil fiyatları ve faiz oranları gibi göstergeler açısından büyük bir önem taşımaktadır. Bu endeksi konu alan çalışmada, 2001 Aralık 2011 Aralık dönemleri arasında, tahvil fiyatlarının dalgalı olduğu, uzun vadeli tahvillerde fiyat dalgalanması ve getirinin daha yüksek oranda olduğu belirtilmiştir. Bunun temel nedeni, uzun vadede tahvil fiyatlarının faiz oranlarındaki artış veya azalışlara karşı daha hassas olmasından kaynaklanmaktadır.

one of the types of financial markets, which help the transfer of the flow of funds, is bond markets. they are mainly preferred by risk-averse investors and contribute to the determination of bond prices, interest rates and long-term investment and financing strategies. in turkey, the bond market is dominated by the public sector because of the borrowing requirement of the state. as a consequence, the bond index is created by considering public securities to demonstrate the developments in the market. government debt security index, which is the only index developed for investors, is significant for indicators such as bond prices and interest rates. in the analysis for the period of december 2001 to december 2011, it is highlighted that bond prices listed on the government debt security index are volatile. moreover, there is higher price volatility and returns for bonds, which have long maturities. the main reason is that in the long term, bond prices are more sensitive to the increases or decreases in interest rates.
Türk devlet iç borçlanma senetleri fiyat endeksi üzerine bir değerlendirme
Keywords: Tarih